Botruanthus mexicanus (Cnidaria: Ceriantharia), a new species of tube-dwelling anemone from the Gulf of Mexico - Stampar, Sérgio N. [UNESP]; González-Muñoz, Ricardo; Morandini, André C. (Springer Nature, 2017)
A second tube-dwelling anemone species of the genus Botruanthus (Cnidaria: Ceriantharia), B. mexicanus sp. nov., was observed in the Veracruz Reef System (1 m depth), Veracruz, Gulf of Mexico, and is described herein. To date, the recorded range of Botruanthus has been restricted to the Pacific Ocean. This new species is the first of this genus reported from the Atlantic Ocean. The number of tentacles, the number of mesenteries attached to the siphonoglyph, and the size of P2 mesentery permit a decisive distinction from Botruanthus benedeni. Some comments are provided, nonetheless, on the difference between Botrucnidifer and Botruanthus, the only two genera of the family Botrucnidiferidae.
Keywords: Botrucnidiferidae; Mexico; Veracruz reef system